Technical analysis backfilling plans of integrated on post mining plan - Suganda Ganda; Restu Juniah; Djuki Sudarmono (Indonesian Journal of Environmental Management and Sustainability, 2018)
PT Samantaka Batubara is one of the coal mining company geographically located in Kecamatan Peranap (Desa Pauh Ranap & Gumanti), Kecamatan Batang Peranap (Desa Punti Kayu), Kabupaten INHU of Provinsi Riau. Based on Minister of energy and mineral resources of the Republic Indonesia number 07 years 2014 on the reclamation and pascatambang, every mining industry must have post-mining planning to obtain mining operation. The objectives of research to know the direction of mining, the volume of pile plan and the design of the embankment. The study refers to the direction of mining from the beginning of 2017 from the southwest side to the end of the mine in 2022 to the northeast. The volume of overburden material stockpiles planned for the post-mining plan program is 2,500,850 LCM in the 1st in 2021 and 3,000,665 LCM periods of the 2nd in 2022 period. The backfilling design in this study follows the recommendation of geotechnical analysis with every 5 meter hump should be formed in a slope angle of 300, with the direction of the heap toward the east. Period prior to entering the post-mining program that is in 2017 the embankment forms the highest elevation of +83 whereas in 2018 to 2020 the highest elevation is flat at +63 elevation. Entering the post-mining period of the highest elevation plan established at +63 elevation in 2021 and 2022.